2018
DOI: 10.4102/aveh.v77i1.455
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error and visual impairment in primary school children in Onitsha, Anambra State, Nigeria

Abstract: Onitsha is an urban area located on the eastern bank of the Niger River in Anambra State, Eastern Nigeria. The study population was primary school children from all the private and Background: Vision problems have been shown to adversely affect a child's achievement in school.Aim: To determine the prevalence of refractive error and visual impairment in primary school children in Onitsha,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
4
18
2
1
Order By: Relevance
“…The prevalence of myopia is highest in our study which is consistent with those reported by Kuma et al in their RE study in private school children in Ghana (Kumah et al, 2013), Naidoo et al in South Africa (Naidoo et al, 2003), Wedner et al in Tanzania (Wedner et al, 2000) and Ngozika et al in Nigeria (Ezinne & Mashige, 2018). This could partly be due to the fact that a non-cycloplegic refraction which reveals less hyperopia and more myopia was used.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of myopia is highest in our study which is consistent with those reported by Kuma et al in their RE study in private school children in Ghana (Kumah et al, 2013), Naidoo et al in South Africa (Naidoo et al, 2003), Wedner et al in Tanzania (Wedner et al, 2000) and Ngozika et al in Nigeria (Ezinne & Mashige, 2018). This could partly be due to the fact that a non-cycloplegic refraction which reveals less hyperopia and more myopia was used.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of 2.1% was higher than that of the 0.32% prevalence reported by Naidoo et al 24 for a study performed in South Africa. A recent study conducted in Nigeria also found a lower prevalence of 1.3%, 32 possibly a result of the fact that they focused on urban children, whilst this study was conducted on rural schoolgoing children. Urban leaners have access to eye care services, †, V/A of worse than 0.32, but better than 0.50.…”
Section: Discussionmentioning
confidence: 68%
“…23,25,26 Although in South Africa, Wajuihian et al 17 did not find any evidence of an association between RE, gender and age, elsewhere myopia has been associated with gender, in some cases with a higher prevalence in girls than boys 14,15,29 and in others a higher prevalence in boys than girls. 30,31,32 As it is known that parents' level of education is also associated with myopia, children of people with post-matric qualifications have been found to be more myopic than children whose parents only have a high school qualification or lower. 26,27 Refractive error is also associated with VI if it remains uncorrected.…”
Section: Introductionmentioning
confidence: 99%
“…This was part of a larger study on RE, VI (Refractive Error Study in Children [RESC]) and utilisation of spectacles amongst primary school children in Onitsha, and a detailed methodology has been described elsewhere. 19 In summary, a stratified random cluster sampling procedure was used to select children aged Myopia was defined as RE of at least −0.50 diopter (D), hyperopia as +2.00 D or more and astigmatism as −0.50 D or more using subjective refraction, whilst utilisation of spectacles was defined as wearing spectacles at the time of examination.…”
Section: Methodsmentioning
confidence: 99%
“…Astigmatism and hyperopia were not significantly associated with age and gender (all p-values > 0.05). Details of the results regarding the prevalence and distribution of REs have been discussed in the RESC Study in Onitsha 19.…”
mentioning
confidence: 99%